Balik Nama Sertifikat Hak Milik Atas Tanah Dalam Jual Beli Tanah Di Kantor Pertanahan Nasional Kabupaten Batang - Muchamad Satria Endriana; Budi Ispriyarso (Magister Kenotariatan Universitas Diponegoro, 2022)
The issue of ownership of land rights became a concern of the government, so that the Basic Agrarian Law was created to regulate the hierarchy of land tenure rights. Ownership of land rights through sale and purchase must be carried out over the name followed by making certificates in the name of the new owner. This article discusses the implementation of reversing the title of title to land title in buying and selling and the obstacles encountered. The method used is normative juridical. The results of this research show that in the process of buying and selling land there are 3 (three) stages, namely preparation before carrying out the process of buying and selling land, making a Sale and Purchase Deed, and reversing the name of the land certificate being traded. The obstacles in the process of changing the name, namely; Standard Operating Procedure (SOP), the process of transferring the name of a certificate whose proof of ownership is still in the form of Letter C Kelurahan, sale and purchase of land rights from inheritance proceeds, unpaid PBB payments, and length of time in processing a certificate at the